(untitled) (OverHolland, 2018)
In October 1970 the Dutch journal Plan published a thematic issue on university education and the construction of universities in the Netherlands. The editorial, entitled ‘Ideology or pragmatism’, outlined the dilemmas facing politicians and designers. Major investment was needed to cope with the growing numbers of students, but there was no clear picture of how education and research should develop. Could the existing universities continue to grow, or should new ones be founded? Should existing universities expand outside cities, or remain in small clusters within them? What was the ideal size of a university? Where should new universities be developed, and what about introducing the Anglo-American campus model? Was the idea of universitas, the supposed unity of arts and science, still relevant? Would university buildings even be needed if lectures could be broadcast on television screens?